Computer-Based Concordancing Courseware for Developing Vocabulary Skills in the ESL Class - Low, Freddie (1994)
The analysis of natural texts provides the basis in which words used in different contexts can be studied. A computer-based concordancing courseware makes the task of analysing natural texts not only viable but also fast. Texts taken from primary sources such as the newspapers, magazines, books, and letters, can be scanned into computer storage devices for analysis later. The study of such a corpus has the advantage of not only providing the student with authentic, natural occurring texts, but also coming out with a list of possible contexts in which the particular word may occur. Forty eight TESL matriculation students in a first semester ESL class studying at Universiti Pertanian Malaysia, Serdang, were randomly assigned to two groups - the experimental group and the control group. Treatment consisted of two stages. In the first stage, the experimental group received the computer concordancing courseware treatment while the control group was taught vocabulary the conventional classroom way. In the second stage, the groups were switched, with the experimental becoming the control group and vice versa. During the treatment period, a set of instructional objectives were adhered to and the learning outcomes pertaining to vocabulary development ensured. The data collected revealed a significant difference in the performance between the control and the experimental groups at the end of stage I. All subjects indicated a positive attitude towards the computer concordancing courseware. Much infonnation was also gleaned on appropriate instructional strategies for integrating computer concordancing into vocabulary teaching.